2008
DOI: 10.1182/blood-2007-11-122945
|View full text |Cite
|
Sign up to set email alerts
|

A shorter von Willebrand factor survival in O blood group subjects explains how ABO determinants influence plasma von Willebrand factor

Abstract: IntroductionPlatelet plug formation at the site of vascular injury is initiated by von Willebrand factor (VWF) interacting with the subendothelial matrix, followed by its binding to platelet glycoprotein (GP) Ib 1,2 and subsequent platelet activation and aggregation. VWF is synthesized by endothelial cells and megakaryocytes, 3,4 and one of its main particular features is a polymer structure ranging in size from 500 000 to more than 20 million Dalton, 5 the largest forms being hemostatically the most efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
241
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(261 citation statements)
references
References 42 publications
14
241
4
2
Order By: Relevance
“…Blood group was known in 51 patients (64%), being O in 34 (43%). Since VWF tends to be lower in individuals with O blood groups 20, we analyzed separately VWF levels in both blood groups, and in spite of everything in GBM patients with O group, the levels were still higher respect to MNGs (median 250 IU/dL, IQR 175.50–355 vs. 164 IU/dL, IQR 121–200). Moreover, the same proportion of O/non‐O blood group was found analyzing separately patients with MNG and those with GBMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood group was known in 51 patients (64%), being O in 34 (43%). Since VWF tends to be lower in individuals with O blood groups 20, we analyzed separately VWF levels in both blood groups, and in spite of everything in GBM patients with O group, the levels were still higher respect to MNGs (median 250 IU/dL, IQR 175.50–355 vs. 164 IU/dL, IQR 121–200). Moreover, the same proportion of O/non‐O blood group was found analyzing separately patients with MNG and those with GBMs.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, we performed a subanalysis in a group of age‐matched GBMs and MNGs, confirming that VWF levels were significantly related with survival irrespective of age. For the same reason, since VWF tend to be higher in individuals with non‐O blood groups 20, we checked that the distribution of ABO blood groups was similar between patients with GBMs and those with MNGs in order to rule out that the increased VWF levels were not attributable to a skewed blood group distribution. Indeed, as reported by Akin, differences in VWF levels between O and non‐O groups are more reliable for VWF values lower than 50 IU/dL, while in our patients, VWF levels are always higher, so as not to show significant differences between ABO groups 29.…”
Section: Discussionmentioning
confidence: 99%
“…al;2008). In current study, the data showed that the plasma vWF/FVIII associated with the brain tumor EPCs and not with the adjacent normal brain EPCs in the astrocytic glioma.…”
Section: Discussionmentioning
confidence: 64%
“…The vWF is a mediator that involved in adhesion of platelets to the collagen and hemostatic plug formation (Spiel et. al;2008). The vWF not only function in the platelet adhesion to the vessel wall but also enhance the platelet to platelet interaction under high shear-stress conditions (Rumbaut et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation